In defense of music: the case for music as argued by a singer and scholar of the late fifteenth century - Harran, Don (Lincoln and London University of Nebraska Press, 1989)
"These are fascinating texts, then; both because they offer us a glimpse of the sorts of arguments which must have raged far more widely than Le Munerat's community, the College de Navarre, and because they shed much incidental light on the performance of chant during the Renaissance." - "Times Literary Supplement". "With his excellent edition and translation of these provocative writings of a little-known fifteenth-century scholastic, Harran has served the wider musical and historical community well." - "JMLA Notes".